FROM THE INQUISITION TO DESCARTES. THE ORIGINS OF THE MODERN SUBJECT - Godzich, Wlad (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
An account of the discursive problematic that accompanies the emergence of the modern subject, and of the difficulties attendant upon that subject's encounter with cultural difference.